Shock between absolutely solid body and elastic bar with the elastic viscous frictional resistance at the side - An, Nguyen Thuc; Trieu, Nguyen Dinh (Vietnam Journal of Mechanics, 1991)
The problem was solved completely in this paper. In the technical point of view this is model of the problem about shock between hammer and pile.